STUDENTS ERRORS ANALYSIS IN CONSTRUCTING NEGATIVE AND INTERROGATIVE SENTENCES BY USING SIMPLE PRESENT TENSE AT THE FIRST GRADE STUDENTS OF SMP SWASTA KARTIKA 1-2 MEDAN - Rahmawati Wati; Ruth Debora Sari Dame Sitompul; Prencis Triiswati Tinambunan; Mirahati Harefa; Helmina Hepi Lismawati Laia (English Education Study Program Faculty of Teacher Training and Education, 2019)
The objectives of this research are to find out the kinds of errors and the dominant error at the first grade students of SMP Swasta Kartika 1-2 Medan in constructing negative and interrogative sentences by using simple present tense in academic year 2019/2020. This research is a qualitative research with a descriptive method. The sample of this research were the first grade students of SMP Swasta Kartika 1-2 Medan with 28 students in VII-3s’ class. The data were gathered by using written test which consisted of 20 questions and were analysed by the researchers with identify each error that made by the students. The findings showed there were 197 (35,55%) case of errors on misformation as a type of dominant; 177 (31,94%) case of errors on omission; 165 (29,78%) case of errors on addition; and 15 (2,70%) case of errors on misordering. In conclusion there were 4 kinds of errors, namely: omission, addition, misformation, and misordering. Where error of misformation was type of dominant errors. Keywords: Error, Error Analysis, Simple Present Tense